Menentukan Titik Rawan Malaria Di Provinsi Nusa Tenggara Timur Menggunakan Metode K-Means Clustering (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Malaria is one of the diseases that is currently affected, but is still a threat and often causes unusual events in NTT province. Malaria in NTT province is the second highest malaria disease in Indonesia after Papua. The method used to analyze the vulnerability to malaria in NTT province is K-Means Clustering. The purpose of analyzing the level of malaria vulnerability is to find out which districts have the highest to lowest vulnerability in NTT province, which is carried out in a geographic information system. The results of the analysis showed tha 7 districts were classified as low malaria vulnerability, 1 district as medium, 12 districts as high and 2 districts as very high. The level of vulnerability can be understood as the level of malaria endemicity.